Biological aspects of Lyme disease spirochetes: unique bacteria of the Borrelia burgdorferi species group - Krupka, Michal; Raska, Milan; Belakova, Jana; Horynova, Milada; Novotny, Radko; Weigl, Evzen (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2007)
BACKGROUND: Borrelia burgdorferi sensu lato is a group of at least twelve closely related species some of which are responsible for Lyme disease, the most frequent zoonosis in Europe and the USA. Many of the biological features of Borrelia are unique in prokaryotes and very interesting not only from the medical viewpoint but also from the view of molecular biology. METHODS: Relevant recent articles were searched using PubMed and Google search tools. RESULTS AND CONCLUSION: This is a review of the biological, genetic and physiological features of the spirochete species group, Borrelia burgdorferi sensu lato. In spite of a lot of recent articles focused on B. burgdorferi sensu lato, many features of Borrelia biology remain obscure. It is one of the main reasons for persisting problems with prevention, diagnosis and therapy of Lyme disease. The aim of the review is to summarize ongoing current knowledge into a lucid and comprehensible form.
Keywords: Borrelia burgdorferi komplex; lymeská nemoc; lidé; Humans; Borrelia burgdorferi Group; Lyme Disease